(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
The distributed database provides a resource sharing environment, where multiple transactions at different sites coexist in order to access the resources. In this paper we investigate multi version locking protocol in distributed environment. Multi-version database has the potential to significantly increase the amount of concurrency in transaction processing as they can avoid read-write conflict by completing the read requests with older versions of data while the write operation is in progress. These algorithms are particularly effective for long queries, which otherwise cannot finish due to the high probability of conflict with other transactions. We have given an improvement on the algorithm proposed by Jie shao. We have not imposed any restriction on the involvement of all the existing sites to obtain a global version which thereby reduces the burden on each individual site. Our scheme involves the collection of local transaction identifier only from the participating site whether it can be one or many. We have proposed our new algorithm to obtain a correct version for a particular data item during read and write operation.